ANALISIS STRUKTURAL NOVEL KIM JI-YEONG LAHIR TAHUN 1982 KARYA CHO NAM-JOO (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
This study describes the structure and interrelationships between elements in the novel Kim Ji-yeong born in 1982 by Cho Nam-joo. The research method used is a qualitative descriptive method with a structural approach. The data generated is in the form of text related to the building blocks of the novel Kim Ji-yeong born in 1982 by Cho Nam-joo published by PT Gramedia Pustaka Utama in 2019 in Jakarta. However, this novel is actually a translated novel from Korean which was published in 2016.